Ketidaksesuaian antara Regulasi dan Praktik Perjanjian Perkawinan Pasca Putusan MK Nomor 69/PUU-XIII/2015 - Fitria Agustin; Meyilin Rosalia Sinaga; Agung Hartono (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the legal regulation of marriage agreements following the Constitutional Court Decision Number 69/PUU-XIII/2015 and to examine the discrepancies between regulations and practices in society. The method used is normative legal research with a statutory and conceptual approach, supported by a literature review from national scientific journals for the period 2021–2025. The results of the first discussion show that the Constitutional Court decision has broadened the regulation of marriage agreements by strengthening the principle of freedom of contract, thus allowing agreements to be made during the course of marriage. However, the results of the second discussion indicate that in practice, these provisions have not been utilized optimally, as evidenced by the low use of post-marriage agreements and the unclear mechanisms for recording and recognizing them by third parties. The conclusion of this study affirms that although legal validity has been fulfilled and contractual freedom has been expanded, its implementation still faces challenges in terms of legal certainty. Therefore, it is recommended to have more detailed technical regulations, enhanced coordination between institutions, as well as legal socialization to the public to support the optimal application of marriage agreements in Indonesia.